An Analysis of Hedonic Behavior Portrayed in Shania Twain’s Selected Song Lyric: English - Imtihan Hanim; Rahmi Aulia Nurdini (Journal of English Development, 2023)
This research aims to describe the hedonism portrayed in Shania Twain’s song. Moreover, it also aims at describing the negative effect of hedonism on young people’s futures. The objective of this study is to analyze the hedonic behavior expressed in the song lyrics and also to describe the negative impact of hedonism, especially for the younger generation, as reflected in the song. "Ka-Ching!" is chosen as the song as it has many hedonistic behaviors, and it is taken as the main research data sung by Shania Twain. Hermeneutic Interpretation theory and Sociology of Literature theory are used. Descriptive qualitative is chosen as a research method. Based on the research, the result shows the types of hedonism expressed in Ka-Ching song lyrics consist of: The results of this research are that (1) the hedonistic issues portrayed in the song lyrics cover aesthetic and egoistic hedonism. These two types dominate the two song lyrics belonging to Shania Twain. The other result is that the ways to anticipate hedonism in life include being wise, being grateful, being simpler in life, and being closer to God.